Bahasa Arab Antara Bahasa Komunikasi dan Bahasa Ilmiah - Pane, Fizri Aspika Putri; Lubis, Iga Nailah Aulia Br; S, Sapri; Kharisma, Mutiara Indah; Salsabila, Nadia; Maibang, Sapriani; Khairani, Yesa Dwi; Siagian, Zaura Izzati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses Arabic between Communication Language and Scientific Language. Arabic is a Semitic language spoken by people inhabiting the Arabian peninsula, and is the oldest language in the world. Arabic is a language that cannot be separated from Islam. This language is often also referred to as the language of Islam. Through qualitative methods with a literature study approach, this research discusses Arabic between the language of communication and scientific language. The results of the research show that (1) Arabic as a language of communication, literary, spoken and written (2) Arabic has become a scientific, academic and popular language in various countries almost on a par with English and French in the era of globalization (3) Maintaining the Arabic language in the digital era must be done by believing that Arabic is the language of the Koran which is a special language, especially for Muslims.